Journal of Biological Engineering - Yoon, Jeong-Yeol; Rao, Raj
Biological engineering is an emerging discipline that encompasses engineering theory and practice connected to and derived from the science of biology, just as mechanical engineering and electrical engineering are rooted in physics and chemical engineering in chemistry. Topical areas include, but are not limited to: Synthetic biology and cellular design Biomolecular, cellular and tissue engineering  Bioproduction and metabolic engineering Biosensors Ecological and environmental engineering Biological engineering education and the biodesign process As the official journal of the Institute of Biological Engineering, Journal of Biological Engineering provides a home for the continuum from biological information science, molecules and cells, product formation, wastes and remediation, and educational advances in curriculum content and pedagogy at the undergraduate and graduate-levels. Manuscripts should explore commonalities with other fields of application by providing some discussion of the broader context of the work and how it connects to other areas within the field.